2006
DOI: 10.1002/adfm.200600262
|View full text |Cite
|
Sign up to set email alerts
|

Bridged Nanocrystals in Biominerals and Their Biomimetics: Classical Yet Modern Crystal Growth on the Nanoscale

Abstract: We demonstrate nanoscale architectures in real biominerals and their biomimetics. Mimicking biomineralization, that is, crystal design in association with organic molecules, has been demonstrated in recent years. Although the macroscopic morphologies in real biominerals and biomimetics have been extensively studied, the nanoscopic structures in terms of the crystal growth are still not fully understood. We show that both materials form oriented architectures of bridged nanocrystals with incorporated organic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
232
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(247 citation statements)
references
References 64 publications
(85 reference statements)
10
232
2
3
Order By: Relevance
“…It was shown that a nacre-mimetic architecture could be synthetically reproduced through an appropriate combination of inorganic crystals and organic polymers (Oaki & Imai 2005;Oaki et al 2006). The specific interactions existing between the two components during crystallization of K 2 SO 4 in the presence of poly(acrylic acid) generate the nanoscopic architecture (20 nm diameter blocks), and the switching between the modes of growth explains the formation of the macroscopic structure (microscopic nacre-like layered structure; Oaki & Imai 2005).…”
Section: Synthetic Strategies To Produce Nacre-based Productsmentioning
confidence: 99%
“…It was shown that a nacre-mimetic architecture could be synthetically reproduced through an appropriate combination of inorganic crystals and organic polymers (Oaki & Imai 2005;Oaki et al 2006). The specific interactions existing between the two components during crystallization of K 2 SO 4 in the presence of poly(acrylic acid) generate the nanoscopic architecture (20 nm diameter blocks), and the switching between the modes of growth explains the formation of the macroscopic structure (microscopic nacre-like layered structure; Oaki & Imai 2005).…”
Section: Synthetic Strategies To Produce Nacre-based Productsmentioning
confidence: 99%
“…The plate-like CaCO 3 crystals are composed of bridged nanocrystals that have a similar orientation. 9 The cooperative involvement of insoluble and soluble macromolecules during crystallization of inorganic compounds seems to be a general strategy in biomineralization. 1 Nacre formation was mimicked by Kato et al [10][11][12][13][14] to synthesize polymer-CaCO 3 thin film composites.…”
Section: Polymer-caco 3 Thin Film Composite Materialsmentioning
confidence: 99%
“…It is inferred that the mesocrystal structures were formed from the following processes. 17 The adsorption of PAA inhibits crystal growth. Because the growth is not completely inhibited by the adsorption of PAA under the supersaturated condition, the growth is restarted by the formation Biomimetic crystal design by molecular control Y Oaki et al of a nanoscale mineral bridge.…”
Section: Proposed Formation Mechanisms Of the Hollow Architecturesmentioning
confidence: 99%
“…In previous works, we found that oriented nanocrystals mixed with organic macromolecules produce macroscopic shapes with single-crystalline orientation. [15][16][17] These mesocrystal structures have attracted considerable interest in recent years. [18][19][20] Learning from biomineralization, mesocrystal structures have been synthesized with synthetic organic molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation